Effects of chitosan versus curcumin on dorsal surface of tongue mucosa of albino rats fed on high-fat diet: histological and ultrastructural study - El- Sayed, Amr Ahmed; Mahmoud, Elham Fathy; Taha, Rasha Mohammed (South Eastern European Journal of Public Health, 2025)
Aim: This work aimed to evaluate the effects of Curcumin versus Chitosan as a natural product on the dorsal surface of tongue mucosa of albino rats fed on high fat diet. Materials and Methods: 40 rats were equally divided into 2 main groups (1- control group: received normal diet and distilled water , 2- experimental groups: divided into 3 subgroups: 2-A received high fat diet, 2-B: received High Fat diet + Curcumin, 2-C: received High Fat diet + Chitosan (curcumin and chitosan were administered to rats via gastric tube). Cholesterol level in blood was measured at day 0, 90 and 120. Rats euthanized at the end of 4 months and tongue specimens were processed for histological and immunohistochemical evaluation. All data were statistically analysed using one-way ANOVA (F) test with post hoc test (Tukey). Results: A high-fat diet caused significant alterations to the tongue's dorsal surface, treatment with curcumin showed a slight improvement. On the other hand, chitosan demonstrated notable improvements to the tongue mucosa. Conclusions: A high-fat diet has a significant cytotoxic effect on the dorsal surface of the tongue. Curcumin and chitosan may have a protective impact on hypercholesterolemia-induced tongue cytotoxicity.